Peran Tokoh Agama Dalam Meningkatkan Partisipasi Umat Untuk Mencegah COVID-19 Di Era Tatanan Normal Baru - Tokan, Pius Kopong; Artama, Syaputra (Universitas Sulawesi Barat, 2022)
Religious activities in the context of this pandemic are often considered a driving factor in the transmission of COVID-19. This study discusses the role of religious leaders in increasing community participation in preventing COVID-19 in the New Normal Order era. public. The study uses a qualitative approach with the aim of describing the role of religious leaders in increasing community participation to prevent Covid-19. The sampling technique used was Snowball with the key informant being the Parish Priest, the main informant: the head of the neighborhood, and the supporting informant: the head of the Community of Basis (KUB). The process of collecting data through interviews, observation and documentation where the main instrument is the researcher himself supported by other instruments. After the data is collected, it is analyzed using the inductive method. The results of the study indicate that the roles that have been fully implemented are preparing the people, conducting health education/counseling, implementing health protocols. Meanwhile, the role that has not been carried out optimally is to build a work system and supervise the implementation of health protocols by the people. It was concluded that in general the Religious Leaders in the St. Parish. Yosef Frainademetz Mautapaga Ende has performed his role well in increasing community participation to prevent COVID-19 in the era of the new normal order.